IMPLEMENTASI E-MODUL BERBASIS LITERASI SAINS TEMA AYO SIAGA BENCANA UNTUK MELATIH KEMANDIRIAN BELAJAR SISWA SMP - Agustin, Salshanabilla; Vitasari, Mudmainah; Resti, Vica Dian Aprelia (PendIPA Journal of Science Education, 2025)
Achieving learning objectives in a successful learning process cannot be separated from one of the students' internal factors, namely independence, especially learning independence. One of the development research that has been carried out by Kristina (2022) is to produce supporting products for teaching materials that can encourage student independence in the form of electronic modules (e-modules). Therefore, efforts are made to implement the E-module to train students' independent learning. This research aims to analyze the implementation of a scientific literacy-based e-module with the theme Let's Prepare for Disasters in training junior high school students' independent learning. The research subjects were class VII students of SMP Negeri 2 Kramatwatu who took science lessons using the e-module. The research method used is descriptive qualitative with data collection techniques in the form of observing learning implementation, observing students' independent learning activities, and learning independence questionnaires. The results of the research showed that the implementation of learning using e-modules went very well, reaching 93.4% at the first meeting and 96.4% at the second meeting. Observations of student learning independence showed an average observation result of 74.3% at the first meeting and 86.1% at the second meeting. Student learning independence questionnaire data supports observation results with an average of 81.1% in the "very good" category. These data show that the e-module based on scientific literacy with the theme Let's Prepare for Disasters is able to effectively train junior high school students' learning independence, as seen from the consistency between learning implementation, student activities in learning independence, and the results of students' perceptions through the learning independence questionnaire.